Chemotherapy is associated with increased survival from colorectal signet ring cell carcinoma with distant metastasis: A Surveillance, Epidemiology, and End Results database analysis. (12th March 2019) - Shi, Tao; Huang, Mengxi; Han, Dong; Tang, Xinyi; Chen, Yanyan; Li, Zhiping; Liu, Chao; Xiang, Dan; Wang, Ting; Chen, Yitian; Wang, Rui; Lei, Zengjie; et al.
Abstract: Background: Colorectal signet ring cell carcinoma (SRCC) is a rare histological subtype of colorectal adenocarcinoma with high metastatic frequency compared to non‐SRCC colorectal cancer (NOS). The aim of this study was to analyze prognostic factors of colorectal SRCC with different metastatic sites and evaluate impacts of various therapies for metastatic colorectal SRCC. Methods: Patients with NOS and SRCC were from the Surveillance, Epidemiology, and End Results (SEER) database during 2010‐2014. χ 2 tests were used to compare data significance. Kaplan‐Meier and COX models were used to analyze the differences in the survival. Propensity‐matched analyses were used to adjust numerical differences. Results: Among the 173 460 patients, 1932 (1.11%) patients had colorectal SRCC. In univariate analysis, older age, male sex, and peritoneum metastasis were associated with higher mortality risk. The peritoneum was both the site with the highest metastatic frequency and the site with the worst prognosis in SRCC. In the COX regression model, peritoneum‐metastatic SRCC patients receiving chemotherapy had better survival than patients treated with surgery. Conclusions: Our study analyzed the unique metastatic pattern of colorectal SRCC toward different sites and found that compared to surgery, chemotherapy was associated with better survival for colorectal SRCC patients with distant metastasis, which provided insights for future SRCC patient treatment. Abstract : The peritoneum was both the site with the highest metastatic frequency and the site with the worst prognosis in colorectal signet ring cell carcinoma patients. Compared to surgery, chemotherapy is associated with better survival for colorectal SRCC patients with distant metastasis, which provided insight for future SRCC patient treatment.